The financial control bodies over the public expenditures in Algeria - Beladjeraf, Samia (Revue jurisprudence, 2019)
The control of the public institutions is an important tool for the State to determine whether it is bound by the law and its commitment to the set limits for it when exercising its activity, and to achieve efficiency in the management and the rationalization of the means so as to realize the objectives established in a general atmosphere of legitimacy and transparency. The methods of control vary in several ways: The judicial supervision, the financial supervision, the administrative control and the political control. However, the effectiveness and the efficiency of the control are related to the extent of the structure, the organization, the framing and the processing of the existing regulators. And the financial supervision through the financial control bodies is considered as one of the most effective methods of control and the most important. It takes four forms which are: The control through the financial controller and the control of the public accountant and the financial supervision by the labor inspectorate and the control through the accounting council. These bodies are capable of eliminating the mismanagement, the poor organization and the dissipation of the public funds which have implications for the projects approved by the state.